2023
DOI: 10.1007/s00428-023-03603-9
|View full text |Cite
|
Sign up to set email alerts
|

Uterine leiomyoma with RAD51B::NUDT3 fusion: a report of 2 cases

Abstract: Three main uterine leiomyoma molecular subtypes include tumors with MED12 mutation, molecular aberrations leading to HMGA2 overexpression, and biallelic loss of FH. These aberrations are mutually exclusive and can be found in approximately 80–90% of uterine leiomyoma, in which they seem to be a driver event. Approximately 10% of uterine leiomyoma, however, does not belong to any of these categories. Uterine leiomyoma with HMGA2 overexpression is the most common subtype in cellular and second most common catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…1 The three main uterine leiomyoma molecular subtypes include, tumors with MED12 point mutations, tumors with biallelic loss of FH, and tumors with HMGA2 overexpression; there are few reports of RAD51B::NUDT3 fusion in leiomyoma. 5,7 There is a wide spectrum of histological variants of leiomyoma including cellular, leiomyoma with bizarre nuclei, mitotically active, Fumarate hydratase deficient (FHDL), hydropic, myxoid leiomyoma, apoplectic, epithelioid, lipoleiomyoma, leiomyoma with lymphoid infiltration and diffuse leiomyomatosis. 1,2,8 LBN was originally regarded as a tumor with a low risk of malignant behaviour, however studies have shown the benign nature of this lesion.…”
Section: Discussionmentioning
confidence: 99%
“…1 The three main uterine leiomyoma molecular subtypes include, tumors with MED12 point mutations, tumors with biallelic loss of FH, and tumors with HMGA2 overexpression; there are few reports of RAD51B::NUDT3 fusion in leiomyoma. 5,7 There is a wide spectrum of histological variants of leiomyoma including cellular, leiomyoma with bizarre nuclei, mitotically active, Fumarate hydratase deficient (FHDL), hydropic, myxoid leiomyoma, apoplectic, epithelioid, lipoleiomyoma, leiomyoma with lymphoid infiltration and diffuse leiomyomatosis. 1,2,8 LBN was originally regarded as a tumor with a low risk of malignant behaviour, however studies have shown the benign nature of this lesion.…”
Section: Discussionmentioning
confidence: 99%